Before the fall [large type] - Hawley, Noah (Grand Central Publishing, 2016)
On a foggy summer night, eleven people--ten privileged, one down-on-his-luck painter--depart Martha's Vineyard headed for New York. Sixteen minutes later, the unthinkable happens: the plane plunges into the ocean. The only survivors are Scott Burroughs--a struggling painter--and a four-year-old boy, who is now the last remaining member of a wealthy and powerful media mogul's family. With chapters weaving between the aftermath of the tragedy and the backstories of the passengers and crew members--including a Wall Street titan and his wife, a Texan-born party boy just in from London, a young woman questioning her path in life, and a career pilot--the mystery surrounding the crash heightens. As the passengers' intrigues unravel, odd coincidences point to a conspiracy: Was it merely dumb chance that so many influential people perished? Or was something far more sinister at work? Events soon threaten to spiral out of control in an escalating storm of media outrage and accusations. And while Scott struggles to cope with fame that borders on noteriety, the authories scramble to salvage the truth from the wreckage.